Review on HPV Vaccines in the Fight Against HPV-Related Cancers - Agabekova, Botagoz; Özler, Nur Banu; Luboteni, Rona (Turkey Health Literacy Journal, 2021)
cases every year, and it is 4.5% of all cancers.By 2017 data HPV prevalence in Turkey is 67.6%. High-risk HPV types cause the development of the cervix, vulva, oropharynx, esophagus, penis, anal cancers. Fortunately, we have methods of preventing cancer formation. The most effective method is vaccination. There are three prophylactic HPV vaccines: 4vHPV (quadrivalent), 2vHPV (bivalent), 9vHPV (nonavailable).The purpose of this review is to investigate HPV cancers and their vaccination. As a result, all three vaccines are similar in terms of dose, efficacy and safety. All are ideally recommended for routine vaccination at 11 or 12 years of age, but the bivalent and quadrivalent vaccines are approved for men and women aged 9 26 years, and the nonavailable vaccine for 9-45 years. Their efficacy was found to be more than 98% for bivalent, 100% for quadrivalent, and 99% for nonavalent. The most important difference between vaccines are HPV types. Bivalent vaccine is effective against Type 16,18, quadrivalent vaccine Type 6,11,16,18, Nonavalan vaccine Type 6,11,16,18,31,33,45,52,58. According to WHO, since 2019 HPV vaccination was included in national vaccination program in 100 countries. We hope that Turkey will be among one of these countries soon.
Keywords: Human Papillomavirus; HPV; Vaccine; Cervical Cancer; Cancer Prophylaxis; Genital Warts